Performance, Carcass Traits and Hematological Parameters of Heat-Stressed Broiler Chicks in Response to Dietary Levels of Chromium Picolinate - Toghyani, M.; Shivazad, M.; Gheisari, A.A.; Zarkesh, S.H. (International Journal of Poultry Science, 2005)
The objectives of this study were to investigate the effects of different levels of chromium picolinate on performance, carcass traits and hematological values of broilers in heat stress condition. Two hundreds and forty male broiler chicks (Ross 308) were allocated to four treatments in a completely randomized design. Treatments supplemented with 0 (control), 500, 1000 or 1500 ppb chromium in the form of chromium picolinate. Each treatment consisted of 4 pens with 15 birds in each pen. The experiment was conducted during summer and all birds were kept under temperature of 33±3°C. Feed intake and body weight were measured at 21 and 42 days of age. At 21 and 42 days of age blood samples were collected from the wing vein of three birds per replicates to determine hematological values. Twelve chicks were slaughtered from each treatment at 42 days of age, and abdominal fat pad, liver, heart, gall bladder and pancreas were removed, weighed and expressed as a percentage of live body weight. Body weight of broilers fed supplemental chromium for 21 and 42 days increased significantly (P< 0.05). Body weight gain and feed intake of broilers fed supplemental chromium increased (P< 0.05). Feed conversion of broilers was not affected by different levels of supplemental chromium. Chromium supplementation increased carcass yield and decreased abdominal fat contents. The hemoglobin, MCH, MCHC were increased by 1000 ppb chromium supplementation. The results from this study suggest that, supplemental chromium, alleviated heat stress related depression in performance, carcass traits and hematological values of broiler chicks.